INFLUENCE OF ROAD CONDITIONS ON CHANGES IN THE TECHNICAL CONDITION OF VEHICLES - Magdiev Sh.P.; Avliekulov Zh.S. (Galaxy International Interdisciplinary Research Journal, 2022)
In hot desert areas, when driving vehicles with driving wheels, especially multi-axle ones, as well as with trailers and semi-trailers, the loosely bound and loose surface layer of the soil is destroyed and shifted, which, under the influence of air turbulences that occur during the movement of the car, significantly saturates the surrounding air with dust.